PENGARUH JOB CHARACTERISTICS dan PERCEIVED ORGANIZATIONAL SUPPORT TERHADAP KINERJA PEGAWAI DINAS KESEHATAN KABUPATEN SEKADAU - ANGGA Hendharsa (Prodi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Panca Bhakti, 2022)
The purpose of this research is to examine and analyze the influence of Job Characteristics and Perceived Organizational Support on the Performance of Sanggau District Health Office Employees. This type of research is included in quantitative research. The population in this study were 58 people, while the samples taken were 58 respondents determined based on the censu technique. The variables in this study consist of independent variables, namely Job Characteristics and perceived organizational support, while the dependent variable is employee performance. Data collection techniques using questionnaires, literature studies and documentation studies. As for the data analysis technique using multiple regression analysis. This research has two output targets to be achieved, namely publishing scientific articles in accredited national or international journals as well as being a reference and media evaluation for the Sanggau District Health Office in an effort to improve the performance of its employees. The results showed that Job Characteristics had a positive effect on employee performance and Perceived Organizational Support had a positive effect on employee Performance of Sanggau District Health Office Employees.